2011
DOI: 10.1037/a0025845
|View full text |Cite
|
Sign up to set email alerts
|

A revised measure of occupational stress for firefighters: Psychometric properties and relationship to posttraumatic stress disorder, depression, and substance abuse.

Abstract: The Sources of Occupational Stress scale (SOOS; Beaton & Murphy, 1993) is a 57-item self-report measure designed to assess the different sources of occupational stress faced by firefighters. The objective of the present research was to develop and evaluate an abbreviated version of the SOOS in order to reduce respondent burden. The revised 14-item version of the SOOS was evaluated in 2 independent samples of firefighters (N = 408) along with measures of job outcomes, posttraumatic stress disorder, depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
54
0
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 27 publications
10
54
0
19
Order By: Relevance
“…Although the vast majority of individuals exposed to traumatic events do not go on to develop PTSD [50], the repeated traumatic exposures inherent in firefighting may serve to enhance the exacerbation of pre-existing vulnerabilities for both PTSD and suicidality, such as AS [51]. Thus, regarding firefighters, it is possible that the distress conferred by repeated occupational exposures (e.g., house fires, medical emergencies, suicide deaths of others; [52,53]) may increase levels of AS. This increase, in turn, may serve to amplify the effects of AS on depression symptoms (which themselves overlap, in part, with PTSD symptoms; [54]) in the prediction of suicide risk, consistent with the propositions of the depression-distress amplification model.…”
Section: Discussionmentioning
confidence: 99%
“…Although the vast majority of individuals exposed to traumatic events do not go on to develop PTSD [50], the repeated traumatic exposures inherent in firefighting may serve to enhance the exacerbation of pre-existing vulnerabilities for both PTSD and suicidality, such as AS [51]. Thus, regarding firefighters, it is possible that the distress conferred by repeated occupational exposures (e.g., house fires, medical emergencies, suicide deaths of others; [52,53]) may increase levels of AS. This increase, in turn, may serve to amplify the effects of AS on depression symptoms (which themselves overlap, in part, with PTSD symptoms; [54]) in the prediction of suicide risk, consistent with the propositions of the depression-distress amplification model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent revisions of the SOOS have indicated that this measure is a reliable and valid assessment of occupational stress among firefighters. 24 …”
Section: Methodsmentioning
confidence: 99%
“…17,18,20 Given that higher levels of stress are known to increase the risk of suicide in general, [26][27][28][29] it is likely that stress also may be a risk factor for suicidal ideation among firefighters, and there is some evidence to support this idea. 13 For example, the large survey of firefighters conducted by NVFC 13 found that perceived stress has a positive association with suicidality (OR = 1.14, p < .001).…”
Section: Stress Social Support and Suicidalitymentioning
confidence: 99%
“…2 Behavioral health disorders, such as depression, posttraumatic stress disorder (PTSD), and alcohol use disorders, are also associated with increased risk for suicidality, 3,4 and this association is also present among firefighters. 13 This association is particularly relevant for firefighters, however, as there is evidence that firefighters are at elevated risk for these and other behavioral health problems, [13][14][15][16][17][18][19] perhaps due to their high levels of occupational stress 17,20 and routine exposure to potentially traumatic experiences. 18,[21][22][23][24] There is also some evidence to suggest that low levels of social support are associated with increased risk for behavioral health problems among firefighters, particularly when firefighters are also high on self-blame.…”
mentioning
confidence: 99%